Design and Implementation of an IEEE 802.11 Signal Quality Monitoring Device Using an OLED Display - Desnalita Ananda; Rudi Arif Candra; Depi Ginting; Arie Budiansyah; T. Sukma Achriadi (Global Advances in Science, Engineering & Technology (GASET), 2025)
Wireless communication based on the IEEE 802.11 standard is widely implemented in Internet of Things (IoT) and wireless network systems. The performance of such systems is strongly affected by signal quality, which directly influences connection stability, data transmission reliability, and latency. This study presents the design and implementation of a portable device for monitoring IEEE 802.11 signal quality using an OLED display. The proposed system is built on an ESP8266/ESP32 microcontroller with an integrated Wi-Fi module, enabling real-time measurement of the Received Signal Strength Indicator (RSSI) from the connected access point. The measured RSSI values are processed and converted into signal quality percentages and classified into qualitative levels, namely excellent, good, fair, and poor. The monitoring results, including SSID, RSSI value, signal quality level, connection status, and IP address, are displayed on a 0.96-inch OLED screen. Experimental testing was conducted under various conditions, including different distances from the access point and the presence of physical obstacles. The results demonstrate that the device is capable of providing accurate and stable signal quality information in real time. The developed system offers a low-cost, portable, and practical solution for wireless network performance evaluation and is suitable for educational purposes, network diagnostics, and IoT deployment analysis.